China’s Conflicting Signals on the South China Sea - Desker, Barry (2016)
China’s position on the South China Sea disputes has been conflicting, if not confusing. Its grand plan to expand cooperative ties with countries along the “One Belt, One Road” initiative could be undermined by its aggressive posture on the South China Sea.